DESAIN MODEL SUMUR RESAPAN UNTUK PENGOLAHAN LIMBAH CAIR RUMAH TANGGA - Hasanah, Andi Uswatun; Buety, Ahmad; Iswadi, Iswadi (Universitas Islam Negeri Alauddin Makassar, 2014)
Fresh and clean water is portable increasingly rare inurban areas.The rivers become the source was contaminated waste of all kinds, ranging from the elimination of organic waste, household hazardous waste to the industry. By adopting this approach the research system of water treatment with domestic sewagerecharge wells.This research was conducted in Garaganti Samata Gowa. This research is set in wells model (two wells model), firsly with tree wells and the secondly in single well which each well containing filtration materials. The results show that significant water outputÂ are colorless, harmless and wasteless both in tree wells by partition and single well Infiltration wellshave two models. This indicated that the wells working good as like as expected. To show the quality and classify of the water output, samples are send to laboratory of Badan Lingkungan Hidup Daerah (BLHD) Province South Sulawesi, with descriptive method presented in tabular form. Result of from BLHD are compared with standart shows that the water output is clean (Peraturan Gubernur No. 69 Tahun 2010 about water quality standard limits an criteria for environmental life damaged), classified in Class III (Peraturan Pemerintah No. 20 Tahun 2010 about water quality and water allocation) and Peraturan Pemerintah No. 82 tahun 2001 about water quality criteria based on class